2009
DOI: 10.1037/a0017118
|View full text |Cite
|
Sign up to set email alerts
|

Appetitively motivated instrumental learning in SynGAP heterozygous knockout mice.

Abstract: The synaptic Ras/Rap-GTPase-activating protein (SynGAP) regulates specific intracellular events following N-methyl-d-aspartate receptor (NMDAR) activation. Here, the impact of SynGAP heterozygous knockout (SG ϩ/Ϫ ) on NMDAR-dependent functions was assessed using different positive reinforcement schedules in instrumental conditioning. The knockout did not affect the temporal control of operant responding under a fixed interval (FI) schedule, but led to a putative enhancement in response vigor and/or disinhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 87 publications
2
13
1
1
Order By: Relevance
“…Collectively, the anomalous changes indicate that hippocampus-specific SynGAP1 loss is sufficient to alter distinct functions known to depend on NMDAR and hippocampal integrity. We have also shown that changes associated with SynGAP1 deficiency cannot be wholly attributed to its malfunction during development by demonstrating similar features with adult hippocampus SynGAP1 knockout (Komiyama et al 2002;Guo et al 2009;Muhia et al 2009Muhia et al , 2010. SynGAP1 therefore continues to play a critical role in adulthood by possibly mediating similar biochemical cascades following NMDAR activation.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Collectively, the anomalous changes indicate that hippocampus-specific SynGAP1 loss is sufficient to alter distinct functions known to depend on NMDAR and hippocampal integrity. We have also shown that changes associated with SynGAP1 deficiency cannot be wholly attributed to its malfunction during development by demonstrating similar features with adult hippocampus SynGAP1 knockout (Komiyama et al 2002;Guo et al 2009;Muhia et al 2009Muhia et al , 2010. SynGAP1 therefore continues to play a critical role in adulthood by possibly mediating similar biochemical cascades following NMDAR activation.…”
Section: Resultsmentioning
confidence: 53%
“…The loss of Syn-GAP1 is associated with alterations in complex behavior and cognitive processes including learning and memory. We and others have recently shown that constitutive heterozygous SynGAP1 deficiency produces multiple behavioral phenotypes ranging from hyperactivity, anxiolysis, cognitive deficits, to altered sensitivity to psychomimetics (Guo et al 2009;Muhia et al 2009Muhia et al , 2010.…”
mentioning
confidence: 99%
“…While its expression in glutamatergic cell is well documented114151629303132, few studies have also reported SYNGAP1 expression in GABAergic neurons173334. To confirm that SYNGAP1 is present in GABAergic neurons, we prepared dissociated neuronal cultures from E18 wild-type embryos and immunostained them for GAD67, which is the main GABA synthesizing enzyme35, and SYNGAP1 at DIV21, after the peak of synapse formation.…”
Section: Resultsmentioning
confidence: 97%
“…Additional phenotypes associated with reduced SynGAP1 levels include marked hyperactivity, impairments of sensory gating, aversive conditioning, social interactions, and working memory (Guo, Hamilton, Reish, Sweatt, Miller et al, 2009), whereas anxiety is reduced (Muhia, Yee, Feldon, Markopoulos, & Knuesel, 2010). Impaired extinction of appetitive conditioning (Muhia, Feldon, Knuesel, & Yee, 2009) and increased sensitivity to thermal pain (Duarte, Duan, Nicol, Vasko, & Hingtgen, 2011) are also observed.…”
Section: Other Psd Scaffoldsmentioning
confidence: 99%
“… *1 Migaud et al, 1998; 2 Yao et al, 2004; 3 Xu et al, 2008; 4 Ehrlich et al, 2007; 5 Nagura et al, 2012; 6 Abbas et al, 2009; 7 Camp et al, 2011; 8 Feyder et al,2010; 9 Carlisle et al, 2008; 10 McGee et al, 2001; 11 Liaw et al, 2008; 12 Welch et al, 2007; 13 Wan et al, 2013; 14 Cuthbert et al, 2007; 15 Coba et al, 2012; 16 Cahill et al, 2009; 17 Xie et al, 2011; 18 Ma et al, 2008; 19 Lemtiri-Chlieh et al, 2011; 20 Kiraly, Eipper-Mains, Ma, & Eippe, 2011; 21 ; Gao et al, 2011; 22 Komiyama et al, 2002; 23 Guo et al, 2009; 24 Muhia et al, 2009; 25 Muhia et al, 2010; 26 Danglot et al, 2012; 27 Sawallich et al, 2009; 28 Kim et al, 2009; 29 Hung et al, 2008; 30 Silverman et al, 2011; 31 Schmeisser et al, 2012; 32 Won et al, 2012; 33 Verpelli et al, 2011; 34 Peca et al, 2011; 35 Yang et al, 2012; 3...…”
Section: Figureunclassified